2005
DOI: 10.1016/j.jmaa.2005.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of population dispersal on the spread of a disease

Abstract: The effect of population dispersal among n patches on the spread of a disease is investigated. Population dispersal does not destroy the uniqueness of a disease free equilibrium and its attractivity when the basic reproduction number of a disease R 0 < 1. When R 0 > 1, the uniqueness and global attractivity of the endemic equilibrium can be obtained if dispersal rates of susceptible individuals and infective individuals are the same or very close in each patch. However, numerical calculations show that populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 19 publications
0
69
0
Order By: Relevance
“…, r} such that v i = v j i . However, this contradicts (11). Summarizing, we showed that the condition (9) for controllability holds.…”
Section: Proofmentioning
confidence: 70%
See 1 more Smart Citation
“…, r} such that v i = v j i . However, this contradicts (11). Summarizing, we showed that the condition (9) for controllability holds.…”
Section: Proofmentioning
confidence: 70%
“…Applying this method, we systematically investigate the intervention strategies of a general SIRS (susceptible-infected-recovered-susceptible) model, that is appropriate for the spread of an infectious disease in a geographically dispersed metapopulation of individuals. While the qualitative properties of metapopulation (patchy) epidemic models have been widely studied in the literature, evaluating the intervention strategies in these models has received less attention (see, for instance, [2,3,6,11,14,18,19] and the references therein). It is particularly challenging to understand the dependence of movement between populations on the reproduction number [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the population size for each species is either assumed to be constant or the per capita birth rate equals the per capita death rate. In other studies, Wang and colleagues [12,14,15] prove global stability of the disease-free and endemic equilibria and verify that the system is uniformly persistent. The Wang and Mulone model [14] is an SIS epidemic model for n patches with a density-dependent births.…”
Section: Introductionmentioning
confidence: 93%
“…Models that include host demography and stochastic effects are especially important for wildlife diseases due to the wide variability in wildlife population sizes. Deterministic metapopulation models for the spread of disease in a multi-patch system have been studied by others [8][9][10][11][12][13][14][15]. In a review article by Arino and van den Driessche [11], the existence and stability of the disease-free equilibrium or endemic equilibria in a variety of different metapopulation models are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], Arino and van den Driessche proposed n-city epidemic models to investigate the effects of inter-city travel on the spatial spread of infectious diseases among cities. In [14], Jin and Wang showed that the n-patch SIS model can be reduced to a monotone system, and the uniqueness and global stability of the endemic equilibrium can be achieved by assuming the dispersal rates of susceptible and infectious individuals are the same. In [21], Li and Shuai investigated an SIR compartmental epidemic model in a patchy environment where individuals in each compartment can travel among n patches.…”
Section: Introductionmentioning
confidence: 99%